049 Hypertension is uncommon during alemtuzumab treatment for relapsing-remit- ting multiple sclerosis. Issue 6 (27th May 2022) - Ong, Hui Ching; Shields, Aoife; Leary, Siobhan; Brownlee, Wallace J
Abstract : Background: Haemorrhagic cerebrovascular events have been reported during Alemtuzumab treatment for relapsing-remitting multiple sclerosis (RRMS) leading to changes in the marketing authorisation in Europe. Hypertension is the proposed mechanism. Aims: To characterise systolic blood pressure (SBP) changes during Alemtuzumab administration and the frequency of significant hypertension. Method: We recorded SBP measurements during Alemtuzumab infusions from a random sample of RRMS patients. Mean SBP changes were calculated for each day and the 5-day treatment course. Common Terminology Criteria for Adverse Events was used to grade hypertension. Results: 2412 SBP measurements from 50 RRMS patients (mean age 35.9 years; 70% female) were recorded. No patients had premorbid hypertension. The mean (SD) SBP change was -0.7 (7.59) mmHg over 5 days. Two (4%) patients developed sustained grade III hypertension (SBP ≥160mmHg) over two or more readings >15 minutes apart, which resolved spontaneously. No patients had immediate cerebrovascular complications. Conclusions: Clinically-significant hypertension is uncommon during Alemtuzumab treatment and should prompt close clinical observation. Slowing (or stopping) the rate of infusion should be considered in patients with sustained hypertension. hui.chingong@nhs.net